Learning from farmer-led access and benefit sharing. Conclusions. - Pistorius, R.; Bruil, J.; Vernooy, Ronnie (Centre for Learning on Sustainable Agriculture (ILEIA), 2016)
This special issue of Farming Matters magazine has explored the ways in which access and benefit sharing of plant genetic resources can work for family farmers. On one hand it presents cases that demonstrate the limited extent to which family farmers have been able to benefit from the ‘formal’ ABS process: the rather complex arrangements between international agreements and national authorities, institutions and communities. On the other hand, this publication uncovers some of the effective principles and mechanisms for access and benefit sharing that are part and parcel of farmers’ everyday practices, even when formal ABS regulations have not yet been designed or implemented.